Determination of IL- 10 gene polymorphism and cytokine level measurement in development of inhibitors among severe haemophilia A patients in Malaysia - K N Vaiappuri, V S Selvavaani (2018)
Haemophilia A is a hereditary X-chromosomal recessive disorder which is characterised by a deficiency of functional factor VIII (FVIII) coagulant activity. Haemophilia can also be classified as severe, moderate or mild based on coagulation factor levels. Patients with severe haemophilia A (FVIII level of < 1%) possess a high risk of spontaneous bleeding. The FVIII concentrates infusion is the treatment of choice for haemophilia A sufferers. However, one of the most unwanted complications is the formation of neutralising antibodies known as inhibitors that will inhibit the clotting activity against the administered factor concentrates in some patients. Patients who develop FVIII inhibitor shows an increase in the frequency of bleeding episodes, which cannot be adequately controlled by FVIII concentrates. They are also at increased risk of morbidity and mortality. There is several mechanisms involved in the formation of inhibitor, i.e. family history, ethnicity, FVIII gene mutations, major histocompatibility complex genotype and polymorphisms of immune-response genes. This study aims to characterise the polymorphism of -592C/A, - 819C/T and -1082G/A in the promoter region of interleukin- l0 (lL-10) and relate them with IL-10 plasma levels. The patients’ whole blood samples and some stored DNA were collected from the National Blood Centre, Kuala Lumpur. The whole blood samples were further processed to obtain the DNA and their serum subjected for IL-10 cytokines level by enzyme-linked immunosorbent assay (ELISA). A total of 64 severe haemophilia A respondents (32 with inhibitors (50%) and 32 without inhibitors (50%)) were involved in this study. Among these respondents, half of the patients (50%) were with high titre inhibitor (≥ 5 BU) and another half (50 %) were low titre inhibitors (<5 BU). The median FVIII inhibitor titre of high and low titre were (Median=38.50, IQR=91 and (Median=1.35, IQR=2.18) respectively. Distribution of respondents according to the ethnicity of Malay, Chinese, and Indian were 65.6%, 26.6% and 7.8% respectively. The overall respondents mean age were 25.03±14.86 years old. The collected DNA that were analysed using the polymerase chain reaction-restriction fragment polymorphism showed that -592A and -819T alleles in the promoter region of IL-10 were observed more frequently in respondents with inhibitors (39 (60.60%) and 40 (66.67%) respectively). However, there was no significant difference of allelic and genotype frequencies of - 592C/A, - 819C/T and -1082G/A in the promoter region of interleukin- l0 (lL-10) among the respondents. These findings showed that there was no significant difference observed between the respondents with and without inhibitors. This suggests a lack of association between the promoter region of the IL-10 gene polymorphisms and the development of inhibitors among patients with severe haemophilia in Malaysia. The -592CA heterozygous genotype were the most prevalent in both Malays and Indians, which had the highest and similar CA genotype percentage of 50% among the patients with inhibitors. The -819CC homozygous genotype was most prevalent among the Malay respondents with inhibitor with the percentage of 9.1%. The -1082 G/A heterozygous genotype were most prevalent among Malay respondents with inhibitor with percentage of 81.8%. Moreover, the high level (Median=98.5 pg/mL, 203.91 pg/mL) of IL-10 concentration were observed among the severe haemophilia A respondents with inhibitors. Elevated level of IL-10 concentration in respondents with inhibitors may suggest an important role for IL-10 in an inhibitor formation. Therefore, larger scale prospective studies are required to confirm these findings.